Effect of the Different Drying Methods on the Chemical Composition of Fluted Pumpkin Leaves (Telfairia occidentalis) - Udoh, Mary Athanasius; Olayemi, Abimbola Gbenga; Onah, Daniel Oche; Yahaya, Musbau Adekunle; Ijezie, Augustina Elochukwu; Umeh, Chukwunonso John-Cyril (African Journal of Medicine, Surgery and Public Health Research, 2025)
Vegetables, primarily the leafy parts of edible plants, are vital sources of essential vitamins and minerals necessary for maintaining good health. Telfairia occidentalis (fluted pumpkin leaves), widely consumed among various ethnic groups in Nigeria, is a green leafy vegetable often subjected to drying for preservation and flavor enhancement. This study aimed to evaluate the impact of drying methods on the chemical composition of T. occidentalis leaves. Approximately 2.5 kg of fresh leaves were procured from Watt Market, Calabar (South-South Nigeria), sorted, and divided into three equal portions: a fresh (untreated) control, a sun-dried sample, and an oven-dried sample. After one month of drying, the samples were pulverized into flour, packaged in airtight containers, and stored in a cool, dry place. Proximate, elemental, and phytochemical analyses were conducted using standard methods. Results revealed a substantial reduction in moisture content from 83.01 ± 0.1% in the fresh sample to 22.60 ± 0.1% and 10.50 ± 0.2% in sun- and oven-dried samples, respectively, leading to increased dry matter. Enhanced concentrations of ash, crude protein, fat, fiber, and carbohydrates were observed, particularly in oven-dried samples (e.g., crude protein increased from 2.80 ± 0.02% to 5.13 ± 0.01%). However, mineral content declined with drying, more significantly in oven-dried samples; sodium levels, for instance, decreased from 9.30 mg/100g (control) to 7.71 mg/100g (sun-dried) and 4.34 mg/100g (oven-dried). Additionally, anti-nutritional factors and food toxicants were significantly reduced, especially in oven-dried leaves. The findings suggest that while drying enhances certain nutritional attributes, it also compromises some mineral content. Nevertheless, drying remains a viable strategy to extend shelf life and reduce waste in the absence of refrigeration.